BUSINESS COMMUNITY EMPOWERMENT: BRANDING OPTIMIZATION, PRODUCT DIVERSIFICATION AND DIGITAL MARKETING - Robiatul Adawiyah; Arika Indah Kristiana (As-Sidanah, 2025)
The Village SDGs are an effort to create a village without poverty and hunger, a village with an even economic growth, a women-friendly village, a networked village, and a culturally responsive village to accelerate the achievement of the Sustainable Development Goals. Dusun Krajan is one of the villages part located at the western tip of Jember Regency. This village is a village that has a variety of potential, both in terms of natural resource potential and the potential for an abundant population. However, this potential cannot yet be utilized optimally. Many residents of Tanggul Wetan Village are still below the poverty line. There are several business communities located in Tanggul Wetan village, especially in Karajan hamlet . Various potential factors and the conditions of the community in this village indicate a deep need to carry out empowerment programs. To achive the Tanggul Wetan Village SDGs, the service team carried out an analysis of the potential and problems that exist in Dusun Krajan. The problem is the knowledge of society especially in Dusun Krajan about how to build a good business is relatively low and there are no socialization or training about how to skill up their potential resources. Based on the results of the problem analysis, the service team from Jember University designed a community service activity, which was packaged in the form of training, guidance and mentoring. or the community to create a village without poverty and hunger. After this community service conducted, the knowledge of the society especially in Dusun Krajan about the branding optimization, product diversification and digital marketing increased.